Using design-based research to improve the lesson study approach to professional development in Camden (London). (15th September 2016) - Brown, Chris; Taylor, Carol; Ponambalum, Lorna
Abstract : The Haverstock Primary to Secondary Transition Project was designed to improve the experience of transition to secondary school for vulnerable pupils in Camden (London). The project used lesson study to help primary and secondary practitioners work collaboratively, to develop effective cross-phase pedagogical approaches to teaching English/literacy and science. This paper has three specific aims in relation to the project. First it reports on how a design-based research (DBR) method was used to tailor the lesson study approach to the Camden context in order to maximize its benefits and ensure its sustainability and scalability. Second it illustrates how a DBR approach to impact assessment led to a radical rethink and understanding of how impact might be measured with regard to projects that involve joint practice development. Specifically, collaborative approaches to practice development rely on more iterative, evolving approaches to understanding and collecting baseline data, developing strategies, and understanding the goals to be reached. Finally, it provides initial data on the impact of the DBR-led lesson study approach.